Risk factors of drug abuse among Malay males FELDA settlers in Jerantut, Malaysia - Mohd Khairi, Amir Faisal; Abdul Rahman, Hejar; Muthiah, Sri Ganesh (JSciMed Central, 2017)
Introduction: Drug abuse places a heavy burden on public health systems in terms of treatment, care, prevention and their health consequences. The objective of this study was to determine risk factors associated with drug abuse among Malay males FELDA settlers in Jerantut, Pahang. Methods: A population based unmatched case control study was conducted in FELDA settlements in Jerantut, Pahang. Cases were defined as confirmed male drug abuser aged 18 to 60 years old. Controls defined as those who had never used any drugs in their lifetime. A total of 180 cases were selected randomly from NADA list, 180 controls were selected randomly from FELDA name list. A self-administered questionnaire was used in this study. Multiple logistic regression analysis was performed using SPSS 22.0. The final model was adjusted for age groups, marital status, education level, employment status, monthly income, smoking status, alcohol consumption, peer influence, self-esteem, family structures, family involvement in drug abuse and religiosity scale. Results: The response rate for case is 180 (89.1%) and 180 (90.0%) for the controls. The final model has a good fit. The highest risk of drug abuse was in age group 20 to 29 years compared to age group 40 to 49 years (aOR=6.93, 95% CI=1.61, 29.83). Those who completed only until primary school had more risk of drug abuse compared to those in tertiary level of education (aOR=11.36, 95% CI=1.78, 72.55). Cigarette smoking had higher risk of drug abuse compared to non-smoker (aOR=10.56, 95% CI=3.14, 35.56). A person who had consumed alcohol had higher risk of drug abuse compared to those who had never consumed alcohol (aOR=9.14, 95% CI=3.75, 22.27). Low self-esteem increases risk of drug abuse compared to normal self-esteem individual (aOR=7.34, 95% CI=3.66, 14.72). High resistance to peer influence was a protective factor for drug abuse (aOR=0.31, 95% CI=0.16, 0.62). Individuals with family members involved in drug abuse had higher risk of being a drug abuse compared to those who had none drug abuse in the family (aOR=4.28,95% CI=1.80,10.17). Conclusion: The risk factors associated with drug abuse are lower education level, smoking, alcohol consumption, low self-esteem, young age, and having family members’ involvement in drug abuse. High resistance to peer influence was a protective factor for drug abuse.